Urgensi Media Pengajaran Dalam Proses Pembelajaran Terhadap Peningkatan Hasil Belajar Murid Di Madrasah Ibtidaiyah Negeri 1 Buton Tengah - Usman Usman (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
This research uses qualitative methods, a type of case study with a single case design. Data collection techniques were carried out using in-depth interviews, participant observation and documentation. Data is analyzed using an interactive model consisting of collecting data (data collection), reducing data (data reduction), presenting data (data display), and concluding (conclusion). Checking the validity of the data is carried out using credibility, transferability, dependability and confirmability tests.This research also aims to find out: (1) Are teaching media urgent in improving learning outcomes, (2) What steps must be taken in the learning process to improve learning outcomes.The results of this research show that: (1) teaching media is very urgent in the learning process in order to improve children's optimal learning outcomes, so that it can make it easier for students to receive lessons, can foster children's learning motivation, (2) Then the steps taken in the learning process To improve student learning outcomes is to provide adequate facilities and infrastructure and carry out the learning process based on the curriculum and local regional conditions using various methods including; lecture method, question and answer method, discussion method, learning assignment method, demonstration method, experimental method, social drama and role playing method, project method and problem solving method